A prognostic gene signature expressed in primary cutaneous melanoma: Synergism with conventional staging - Brunner, Georg; Heinecke, Achim; Falk, Thomas M.; Ertas, Beyhan; Bloedorn-Schlicht, Norbert; Schulze, Hans-Joachim; Suter, Ludwig; Atzpodien, Jens; Berking, Carola (JNCI Cancer Spectrum, 2018)
Background: Current clinico-pathological American Joint Committee on Cancer (AJCC) staging of primary cutaneous melanoma is limited in its ability to determine clinical outcome, and complementary biomarkers are not available for routine prognostic assessment. We therefore adapted a gene signature, previously identified in fresh-frozen (FF) melanomas and adjacent stroma, to formalin-fixed paraffin-embedded (FFPE) melanomas. The aim was to develop a gene expression profiling (GEP) score to define patient survival probability at the time of first diagnosis. Methods: Expression of 11 FF melanoma signature genes was quantified by reverse transcription polymerase chain reaction in an FFPE melanoma training cohort (n = 125), corresponding to the combined FF melanoma training and validation cohorts. The resulting GEP score was validated technically and clinically in an independent FFPE melanoma cohort (n = 211). All statistical tests were two-sided. Results: We identified a prognostic eight-gene signature in the tumor area (tumor and adjacent tissue) of AJCC stage I-III melanomas. A signature-based GEP score correlated with melanoma-specific survival (MSS; Kaplan-Meier analysis: P < .0001) was independent of tumor stage (multivariable regression analysis: P = .0032) and stroma content ( < 5% - 90%) and complemented conventional AJCC staging (receiver operating characteristic curve analysis: area under the curve = 0.91). In the clinical validation cohort, the GEP score remained statistically significant (P = .0131) in a multivariable analysis accounting for conventional staging. The GEP score was technically robust (reproducibility: 93%; n = 84) and clinically useful, as a binary as well as a continuous score, in predicting stage-specific patient MSS. Conclusions: The GEP score is a clinically significant prognostic tool, contributes additional information regarding the MSS of melanoma patients, and complements conventional staging.
CRIS-Team Scopus Importer:2023-03-23